Observing Convection in Microgravity - Heer, Matt (Proceedings of the Wisconsin Space Conference, 2012)
The purpose of the experiment is to observe the movement, or lack thereof, of heat in an enclosed space in multiple gravitational accelerations. An electric heat source will be placed in the center of an insulated box and three temperature probes above and below the heating element at equal spacing will record temperature variations every hundredth of a second. It will be placed on a KC-135 airplane that does a series of parabolas that provide an acceleration of 0G (or microgravity) similar to that of astronauts on the space station, and 2G on its return climb. On earth heat is dispersed unevenly due to cold air being denser therefore getting pulled down by gravity. In a micro gravitational environment there is nothing to cause this shift. During the microgravity phase of our experiment, we expect to initially see symmetry in the temperatures (ie temperature probe C and D are the same, B and E are the same, A and F are the same. See Illustration 1). As the plane goes into its 2 G phase, we expect to see heat rise. (ie probe A is hottest, B next hottest, and continuing with that pattern with probe F being coldest)Â